Assessing immune factors in maternal milk and paired infant plasma antibody binding to human rhinoviruses - Vera, Jessica M.; McIlwain, Sean J.; Fye, Samantha; Palmenberg, Ann; Bochkov, Yury A.; Li, Hanying; Pinapati, Richard; Tan, John C.; Gern, James E.; Seroogy, Christine M.; Ong, Irene M. (Frontiers in Immunology, 2024)
Before they can produce their own antibodies, newborns are protected from infections by transplacental transfer of maternal IgG antibodies and after birth through breast milk IgA antibodies. Rhinovirus (RV) infections are extremely common in early childhood, and while RV infections often result in only mild upper respiratory illnesses, they can also cause severe lower respiratory illnesses such as bronchiolitis and pneumonia. We used high-density peptide arrays to profile infant and maternal antibody reactivity to capsid and full proteome sequences of three human RVs -A16, B52, and C11. Numerous plasma IgG and breast milk IgA RV epitopes were identified that localized to regions of the RV capsid surface and interior, and also to several nonstructural proteins. While most epitopes were bound by both IgG and IgA, there were several instances where isotype-specific and RV-specific binding were observed. We also profiled 62 unique RV-C dominant protein loop sequences characteristic of this species' capsid VP1 protein.Many of these RV-C sites were highly bound by IgG from one-year-old infants, indicating recent or ongoing active infections, or alternatively, a level of cross-reactivity among homologous RV-C sites.